2018
DOI: 10.1136/gutjnl-2017-315082
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence rate of digestive tract bacteria in duodenoscopes: a nationwide study

Abstract: ObjectiveIncreasing numbers of outbreaks caused by contaminated duodenoscopes used for Endoscopic Retrograde Cholangiopancreatography (ERCP) procedures have been reported, some with fatal outcomes. We conducted a nationwide cross-sectional study to determine the prevalence of bacterial contamination of reprocessed duodenoscopes in The Netherlands.DesignAll 73 Dutch ERCP centres were invited to sample ≥2 duodenoscopes using centrally distributed kits according to uniform sampling methods, explained by video ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 28 publications
6
116
0
10
Order By: Relevance
“…Consistent with previous reports, the most common cause of scope contamination was found to be human factors [1,5,13,14]. Despite the complex design of the duodenal scope and recent concerns about duodenal scope contamination [3,5,15,16], duodenal scopes showed a lower scope contamination rate in our study compared with those in previous reports [7,17,18] and the frequency of microbiology surveillance should be the same regardless the type of endoscope. A monthly culture of all endoscopes in our unit helped to detect scope contamination and pinpoint the step in the endoscope reprocessing procedure in which contamination occurred.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous reports, the most common cause of scope contamination was found to be human factors [1,5,13,14]. Despite the complex design of the duodenal scope and recent concerns about duodenal scope contamination [3,5,15,16], duodenal scopes showed a lower scope contamination rate in our study compared with those in previous reports [7,17,18] and the frequency of microbiology surveillance should be the same regardless the type of endoscope. A monthly culture of all endoscopes in our unit helped to detect scope contamination and pinpoint the step in the endoscope reprocessing procedure in which contamination occurred.…”
Section: Discussionsupporting
confidence: 89%
“…Endoscopy-associated infection has become an important issue since the outbreak of carbapenem-resistant Enterobacteriaceae (CRE) infection after endoscopic retrograde cholangiopancreatography in the USA between 2012 and 2015 [4]. These outbreaks resulted in efforts to investigate the quality and e cacy of endoscope reprocessing, as well as factors that in uence transmission between endoscopes and patients [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the FDA letter stated that infectious outbreaks of multidrug-resistant bacterial contamination of duodenoscopes were reported in duodenoscopes with a fixed distal cap [25]. Another nationwide study by Rauwers et al evaluated the prevalence of bacterial contamination of 10 different duodenoscope types and designs, including the elevator channel and the distal cap, and found that the contamination was not associated with one particular duodenoscope type (P ≥ 0.20) [26]. This led manufacturers to design duodenoscopes with detachable caps in order to reduce the risk of contamination at the elevator site.…”
Section: Discussionmentioning
confidence: 99%
“…Recent cases of cross‐infection with carbapenem‐resistant organisms have been reported and, in some cases, despite apparently appropriate disinfection technique . A national audit in the Netherlands studied contamination in ready‐to‐use duodenoscopes and found 15% to be contaminated with enteric organisms . Guidelines aimed at minimizing this problem have been published but cross‐infection will remain a serious concern until endoscopic equipment can be sterilized.…”
Section: Cross‐infection the Achilles Heel Of Endoscopymentioning
confidence: 99%